Simulated work loops predict maximal human cycling power - Martin, J. C.; Nichols, J. A. (The Journal of Experimental Biology, 2018)
Fish, birds and lizards sometimes perform locomotor activities with maximized muscle power. Whether humans maximize muscle power is unknown because current experimental techniques cannot be applied non-invasively. This study leveraged simulated muscle work loops to examine whether voluntary maximal cycling is characterized by maximized muscle power. The simulated work loops used experimentally measured joint angles, anatomically realistic muscle parameters (muscle-tendon lengths, velocities and moment arms) and a published muscle model to calculate power and force for 38 muscles. For each muscle, stimulation onset and offset were optimized to maximize muscle work and power for the complete shortening/lengthening cycle. Simulated joint power and total leg power (i.e. summed muscle power) were compared with previously reported experimental joint and leg power. Experimental power values were closely approximated by simulated maximal power for the leg [intraclass correlation coefficient (ICC)=0.91], the hip (ICC=0.92) and the knee (ICC=0.95), but less closely for the ankle (ICC=0.74). Thus, during maximal cycling, humans maximize muscle power at the hip and knee, but the ankle acts to transfer (instead of maximize) power. Given that only the timing of muscle stimulation onset and offset were altered, these results suggest that human motor control strategies may optimize muscle activation to maximize power. The simulations also provide insight into biarticular muscle function by demonstrating that the power values at each joint spanned by a biarticular muscle can be substantially greater than the net power produced by the muscle. Our work-loop simulation technique may be useful for examining clinical deficits in muscle power production.